社区种子库:农民手册.第1册.建立种子库 - Vernooy, Ronnie; Bessette, Guy; Sthapit, Bhuwon R.; Dibiloane, Angeline; Lettie Maluleke, Nkat; Abner Matelele, Lehlogonolo; Mokoena, Mpolokeng Lydia; Phora, George; Sema, Precious; Thabo, Tjikana (Bioversity International and the International Center for Tropical Agriculture, 2021)
Chinese version of How to develop and manage your own community seed bank: Farmers’ handbook (updated version). Establishing a community seed bank: Booklet 1 of 3. This handbook is a companion to Vernooy, R., Sthapit, B. and Bessette, G. (2020). Community seed banks: concept and practice. Facilitator handbook (updated version). Bioversity International, Rome, Italy (https://hdl.handle.net/10568/81286). The three booklets making up this handbook were written and designed for rural producers who are interested in establishing, supporting, and managing a community seed bank. Each booklet focuses on a theme presented by the members of a community seed bank in Africa, Asia, and Latin America. Booklet 2 of 3 (Chinese) can be found here: https://hdl.handle.net/10568/113974. Booklet 3 of 3 (Chinese) can be found here: https://hdl.handle.net/10568/113975. Translation and adaptation to the local language is encouraged. If you would like to receive a hard copy of the booklets or give feedback or suggestions for improvement, please contact r.vernooy@cgiar.org.